Association of FTO and PPARG polymorphisms with obesity in Portuguese women - Carlos, Fábio Ferreira (2013)
Purpose: We evaluated the association between risk of obesity in the Portuguese population and two obesity-related single-nucleotide gene polymorphisms: fat-mass and obesity-associated (FTO) rs9939609 and peroxisome proliferator-activated receptor gamma (PPARG) rs1801282. Patients and methods: A total of 194 Portuguese premenopausal female Caucasians aged between 18 and 50 years (95 with body mass index [BMI] ≥30 g/m2, 99 controls with BMI 18.5–24.9 kg/m2) participated in this study. The association of the single-nucleotide polymorphisms with obesity was determined by odds ratio calculation with 95% confidence intervals. Results: Significant differences in allelic expression of FTO rs9939609 (P<0.05) were found between control and case groups, indicating a 2.5-higher risk for obesity in the presence of both risk alleles when comparing the control group with the entire obese group. A fourfold-higher risk was found for subjects with class III obesity compared to those with classes I and II. No significant differences in BMI were found between the control and case groups for PPARG rs1801282 (P>0.05). Conclusion: For the first time, a study involving an adult Portuguese population shows that individuals harboring both risk alleles in the FTO gene locus are at higher risk for obesity, which is in agreement to what has been reported for other European populations.